An Optimal Control Problem Governed by a Kirchhoff-Type Variational Inequality - Chengfu Wang; Pengcheng Wu; Yuying Zhou (Journal of Applied Mathematics)
This paper is concerned with an optimal control problem governed by a Kirchhoff-type variational inequality. The existence of multiplicity solutions for the Kirchhoff-type variational inequality is established by using some nonlinear analysis techniques and the variational method, and the existence results of an optimal control for the optimal control problem governed by a Kirchhoff-type variational inequality are derived.